2017
DOI: 10.1016/j.jor.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiological evaluation of retear rate in arthroscopic double row versus single row repair technique in full thickness rotator cuff tear

Abstract: Retear rate is low in double row repair technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Many previous studies have shown that the double-row repair technique can achieve stronger fixation and a lower rotator cuff retear rate. 25,27,55 The results of this study suggest that the repair technique (single row or double row) is not a risk factor for rotator cuff retear after ARCR. Based on the results of this study and considering the clinical practicability and the economic ability of patients, a single-row suture technique with relatively low cost and technical difficulty can be selected.…”
Section: Intraoperative Factorsmentioning
confidence: 69%
“…Many previous studies have shown that the double-row repair technique can achieve stronger fixation and a lower rotator cuff retear rate. 25,27,55 The results of this study suggest that the repair technique (single row or double row) is not a risk factor for rotator cuff retear after ARCR. Based on the results of this study and considering the clinical practicability and the economic ability of patients, a single-row suture technique with relatively low cost and technical difficulty can be selected.…”
Section: Intraoperative Factorsmentioning
confidence: 69%
“…The internal validity of the trial is further ensured by: minimising bias by use off an online computer-based randomising system, blinding of patients and outcome accessors, use of appropriate statistical testing, blinded data interpretation and an adequate sample size based on a power calculation. In addition to the patient-related factors, the repair technique of the tear can influence the final outcome and retear rates according to reports of patient series 62 63. However, the latest meta-analyses showed no sound evidence on the difference in clinical outcome or retear rates between single and double row repair in small to medium sized (<3 cm) tears 64–67.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the following 11 variables that have been previously reported: age 8,21 ; AP tear width and mediolateral tear length 2,8,14,16,18,20,21 ; fatty infiltration of the rotator cuff muscles (ie, supraspinatus, infraspinatus, and subscapularis) and global fatty degeneration index 2,8,17,21 ; CSA 12,22 ; hyperlipidemia, 13 cholesterol level, diabetes mellitus, 8 and smoking 26 ; and surgical technique (ie, single-row, double-row, and suture bridging). 4,6,15,27,30 Hyperlipidemia and diabetes mellitus were defined by the primary care physician who treated the patient at the time of evaluation. The cholesterol and glycated hemoglobin (HbA1c) levels were based on preoperative blood test data.…”
Section: Outcome Measuresmentioning
confidence: 99%